A Provider-Focused Intervention to Promote Optimal Care of Pediatric Patients With Suspected Elbow Fracture. Issue 12 (24th December 2021) - Diaz, Maria Carmen G.; Werk, Lloyd N.; Crutchfield, James H.; Handy, Lori K.; Franciosi, James P.; Dent, Joanne; Villanueva, Raymond; Antico, Eileen; Taylor, Alex; Wysocki, Tim
Abstract : Objective: Emergency department (ED) and urgent care (UC) physicians' accurate assessment of the neurovascular and musculoskeletal (NV/MSK) examination in pediatric patients with suspected elbow fracture is crucial to the early recognition of neurovascular compromise. Our objective was to determine the impact of computer-based simulation (CBS) and computerized clinical decision support systems (CCDSS) on ED and UC physicians' assessment of the NV/MSK examination of pediatric patients with elbow fracture as noted in their documentation. Methods: All ED UC physician participants received CBS training about management of pediatric patients with suspected elbow fracture. Participants were then randomized to receive CCDSS (intervention arm) when an eligible patient was seen or no further intervention (comparison arm.) Participants received feedback on the proportion of patients with discharge diagnosis of elbow fracturewith proper examination elements documented. Results: Twenty-eight ED and UC physicians were enrolled — 14 in each arm. Over the span of 16 weeks, 50 patients with a discharge diagnosis of elbow fracture were seen — 25 in each arm. Twenty-two of 25 (88%) patients seen by intervention arm participants had a complete NV/MSK examination documented. Six of 25 (24%) patients seen by comparison arm participants had a complete NV/MSK examination documented. Elements most commonly missed in the comparison arm included documentation of ulnar pulse as well as radial, median, and ulnar nerve motor functions. Conclusions: Compared with single CBS training alone, repeated exposure to CCDSS after CBS training resulted in improved documentation of the NV/MSK status of pediatric patients with elbow fracture.